Insight of Corporate Social Responsibility Aftermath Covid -19 Pandemic in India - Vats, Richa; Mittal, Shikha (Journal of Commerce and Trade, 2021)
Corporate social responsibility is an act of companies, whereby they demonstrate their benign attitude towards the society and contribute for the development of communities that survive in the nearby vicinity of the institutions, in which they operate or have establishment for production or manufacturing. Indian businesses have known the concept of philanthropy and they have been practicing it to share the wealth that they have gained and accumulated by doing business in the community that they serve in. In modern times also Indian businesses have set examples in their conduction of business. Moreover, it has become the first ever country in the whole world, which has legalized the norms pertaining to the conduction of corporate social responsibility in India. These norms have made it legally mandatory to follow the norms, which are to direct the initiatives that are to be taken up the corporate houses of India and the procedure that has to be followed for the same. The basic aim of paper is to gain insight into the norms that are provided by the legal mandate pertaining to the corporate social responsibility and the initiatives that have been taken up by the companies and corporate of India for the assistance of central and state government in their fight with COVID-19. Classification-JEL : C83, M18